1988
DOI: 10.1002/jlac.198819880605
|View full text |Cite
|
Sign up to set email alerts
|

Struktur und Geruch, VII. Synthese und olfaktorische Eigenschaften von Theaspiran‐Analoga

Abstract: nic SPirodiliydroruuranc 8-12 wurdcn durch Addition der jcwiligrn Alkinole an das Kcton 20 (+ 21 -25). Lindlar-Hydrier u n 3 I---26-30) und Cyclisicrung hcrgcstellt. -Die gesittigten Dcriviitc 1-6 warcn entwcdcr durch Hydricrung (8-10 -+ 1. 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…It emanates a fresh, fruity odor with a strong blackcurrant impact and an additional camphoraceous tonality. Despite extensive research in this family, [6][7][8][9][10] no seco-structures have yet been prepared. From the spiro-systems studied, it was only known that a 2-Me group was crucial, 7,8 and that a C 3 =C 4 double-bond could intensify the blackcurrant odor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It emanates a fresh, fruity odor with a strong blackcurrant impact and an additional camphoraceous tonality. Despite extensive research in this family, [6][7][8][9][10] no seco-structures have yet been prepared. From the spiro-systems studied, it was only known that a 2-Me group was crucial, 7,8 and that a C 3 =C 4 double-bond could intensify the blackcurrant odor.…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive research in this family, [6][7][8][9][10] no seco-structures have yet been prepared. From the spiro-systems studied, it was only known that a 2-Me group was crucial, 7,8 and that a C 3 =C 4 double-bond could intensify the blackcurrant odor. 8,9 An important dihydrofuran is Etaspirene ® (6), a captive used for instance in the female fine fragrance 'Pleasures' (E. Lauder, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, transposed enones can be formed as minor compounds,274 and a few times the oxidative transposition can predominate over the normal oxidation of primary or secondary alcohols 275. The main product results from an uneventful oxidation of a primary alcohol.…”
mentioning
confidence: 99%
“…9 However, it has been reported that lithiated acetone cyclohexylimine condensed with 2,6,6-trimethyl-2-cyclohexenone to give the 1,2-adduct (eq 17). 23 Lithiated acetone cyclohexylamine gives a 9,10-adduct with acridine (eq 18 Lithiated acetone isopropylimine adds to the double bond of α-(N-methyl-N-phenylamino)acrylonitrile to give the Michael adduct, which is alkylated and ring closed to afford 2,5-dimethyl-1-isopropylpyrrole (eq 19). The reaction of acetone cyclohexylamine with Methyl Acrylate without added base has been investigated in detail.…”
mentioning
confidence: 99%